2022
DOI: 10.1088/2053-1583/ac58a1
|View full text |Cite
|
Sign up to set email alerts
|

Device level reversible potassium intercalation into bilayer graphene

Abstract: Electrochemical intercalation and storage of alkali metal ions into the graphite interlayer space is a key ingredient for commercial rechargeable ion batteries. While this has been exceptionally fruitful for lithium, the use of other more abundant chemical species such as potassium has fallen behind due to their less favorable ionic radius and host-guest interactions. Here, we deploy a device level on-chip cell architecture to study the reversible intercalation of potassium into the single van der Waals galler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Bilayer graphene also holds promising applications in the field of energy storage and is anticipated to emerge as a favorable electrode material for secondary batteries. Several studies on the fundamental properties of doped bilayer graphene have been reported previously. Besides, bilayer graphene codoped with FeN 4 –HfN 4 and FeN 4 –IrN 4 has been reported for its remarkable catalytic prowess in the realms of HER, OER, and ORR . The bilayer heterojunction composed of CoN 4 -embedded graphene and B-doped graphene has been documented to exhibit outstanding oxygen reduction electrocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Bilayer graphene also holds promising applications in the field of energy storage and is anticipated to emerge as a favorable electrode material for secondary batteries. Several studies on the fundamental properties of doped bilayer graphene have been reported previously. Besides, bilayer graphene codoped with FeN 4 –HfN 4 and FeN 4 –IrN 4 has been reported for its remarkable catalytic prowess in the realms of HER, OER, and ORR . The bilayer heterojunction composed of CoN 4 -embedded graphene and B-doped graphene has been documented to exhibit outstanding oxygen reduction electrocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%